Scientific and methodological approach to the evaluation of the potential of economic activities types. (Economics and region, 2018)
The article investigates the features of the construction of scientific and methodical approach to the potential assessment of economic activities. Calculated integrated index takes into account the positive impact that each type of economic activity has on economic and social components of national development, as well as a destructive influence of environmental component on sustainable development of the country. The practical calculation of potential of economic activities in Ukraine showed a significant reserve to the increase of this indicator provided to minimize the damage caused to the environment.
Keywords: potential; types of economic activities; reference; environmental component; quasi- distances